Composition of Amphibian Assemblages in Agroecosystems from the Central Region of Argentina - Bionda, Clarisa de Lourdes (2011)
The anuran diversity, abundance, richness and evenness were examined in agroecosystems from the central region of Argentina, area that was greatly altered by agricultural activities. Relationships with climatic characteristics were also analyzed. To capture anurans, pitfall trap transects were established. A total of 561 amphibians of seven species, belonging to four families (Bufonidae, Leiuperidae, Cycloramphidae, and Leptodactylidae) were recorded. Stepwise multiple linear regressions showed strong positive association between both species richness and anuran abundance with habitat variables as rainfall and rain-day. The anuran richness observed in the studied areas is similar to other sites with level of alteration comparable, but the anuran richness and abundance observed here is lower compared with the records of anuran species for the region before agricultural development. Thus, these results have suggested that amphibians may be particularly affected by habitat modification and degradation due to agricultural activities in the central region of Argentina, and it may be contributing to regression of their diversity and richness.